Atomically Dispersed Pt-Ru Dual-Atom Catalysts for Efficient Low-Temperature CO Oxidation Reaction - Qi, Yanan; Chen, Hongqiu; Hong, Feng; Cai, Xiangbin; Ying, Zhehan; Diao, Jiangyong; Jia, Zhimin; Chen, Jiawei; Wang, Ning; Xiang, Shengling; Chen, Xiaowen; Wen, Guodong; et al. (Nano-Micro Letters, 2026)
Single-atom catalysts (SACs) have demonstrated excellent performance in heterogeneous catalytic reactions owing to their maximized atomic efficiency, distinctive geometric, and electronic configurations. However, the efficacy of SACs remains limited for certain reactions requiring simultaneous activation of multiple reactants over metallic active sites. Herein, we report an atomically dispersed Pt1Ru1 dual-atom pair site anchored on nanodiamond@graphene (ND@G) for CO oxidation. The Pt1Ru1 dual-atom catalyst shows an exceptional turnover frequency (TOF) of 17.6 × 10−2 s−1 at significantly lower temperature (30 °C), achieving a tenfold increase in TOF compared to single-atom Pt1/ND@G catalyst (1.5 × 10−2 s−1) and surpassing to previously reported Pt-based catalysts under similar conditions. Moreover, the catalyst demonstrates excellent stability, maintaining its activity for 40 h at 80 °C without significant deactivation. The superior catalytic performance of Pt-Ru dual-atom catalysts is attributed to the synergistic effect between Pt and Ru atoms with enhanced metallicity for improving simultaneous adsorption and activation of CO and O2, and the tuning of conventional competitive reactant adsorption into a non-competitive pathway over dual-atom pair sites. The present work manifests the advantages of dual-atom pair sites in heterogeneous catalysis and paves the way for precise design of catalysts at the atomic scale. Highlights: 1 We successfully fabricated an atomically dispersed dual-atom catalyst featuring Pt1-Ru1 sites anchored on defective graphene (Pt1Ru1/ND@G). 2 Pt1Ru1/ND@G achieves a high turnover frequency of 17.6 × 10−2 s−1 for CO oxidation at 30 °C, which is 10 times higher than Pt1/ND@G and demonstrates outstanding performance compared with the previous reports. 3 Pt-Ru bond enhances the metallicity of both Pt and Ru atoms, facilitating the simultaneous adsorption and activation of CO and O2 and overcoming the limitations of single-atom catalysts.